The analysis of state and efficiency of entrepreneurial activity’s development of the Pavlodar region - Kashuk, L.I.; Bekniyazova, D.S.; Soltangazinov А.R. (BUKETOV BUSINESS REVIEW, 2018)
In the article, on the materials of the Pavlodar region, the state of the sphere of small and medium-sized entrepreneurship (SME) is analyzed in the context of the main socially significant indicators of its development. The analysis’ materials show a number of stable patterns of SME development in the region, both positive and negative. Among them, the reduction in the number of registered, operating and active SME subjects is observed in the article, which is reflected in the dynamics of the population engaged in this sphere, the volume of production and the contribution of this sector of the economy to the gross regional product. Identification of the reasons of the formation of the negative trend of reduction of the number of active SME subjects in the article is carried out in the context of the structural components of the subjects of this sphere. The analysis testifies to the existence of a number of disproportions in the development of SME in the region: structural ones in the combination of SME subjects there is dominated the category of «small entrepreneurship», which is represented maximally by individual entrepreneurs in the context of the organizational and legal forms of SME in the region, and in the context of economy branches - by trade; territorial: the maximum number of SME subjects in the region is concentrated in urban settlements and, first of all, in the regional center, Pavlodar c. Despite the measures taken by the state, including support for the cooperative movement, among the main problems of the entrepreneurs of the region are infrastructural, financial and tax problems. Considering the fact that the tendencies and problems of SME development in the region are illogical to the situation in the whole in the republic, their solution, first of all, requires macroeconomic regulation and balanced situational approach to their solution in the region.